Attractive solutions and traps for catching Musca domestica L. 1758 (Diptera: Muscidae) - Santos, José Lucas Guilherme; Menezes, Hudson Ellen Alencar; Silva, José Carlos Santos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
The house fly Musca domestica L.,1758 (Diptera: Muscidae) is a vector of several pathogens for humans and animals. The control flies in homes and industries generally takes place through chemical products. However, the capture of the se insects can be performed using diferente methods, including traps containing food attractants. Thus, the objective of this study was to evaluate the use of attractive solutions and the developmento fartisantraps for the capture of M. domestica as a way to reduce the use of insecticides. Four solutions were tested as attractants for feeding house flies: brown sugar solution (10%); mango juice (30%), guavajuice (30%) and pine aple juice (30%),10% of the solution with brown sugar was added to each juice; and five sampling times: to the 4 days of experiment, 8 days of experiment, 12 days of experiment, 16 days of experiment and to the 20 days of experiment. The experiment design adopted was a randomized block design, with treat ments arranged in a 4 x 5 factorial scheme, with four replications. The results of the present study allow us to infer that artisanal traps containing food solutions with brown sugar (10%) are the most effective in capturing M. domestica, however, guava and pineapple juices are not different in attractiveness.